(untitled) (Proceedings of the International Conference on Poverty and Sustainable Development, 2019)
Tourism increasingly become a tool to achieve sustainable development, especially in the perspective of poverty alleviation. Indeed, increasing international tourism receipt is probably recognized as the most readily way to reduce poverty. Despite the significant amount of strategy research eager to lessen poverty by adopting tourism, there is little understanding of what effects tourism has on poverty alleviation on a macro level, especially at different poverty levels. This study considered the effect of tourism growth on poverty alleviation in 66 developing countries from 1995 to 2012. The analysis focused on the GDP growth rate, international tourism receipts, international tourism arrivals, absolute poverty headcount ratio, and the application of linear and panel quantile regression techniques to the poverty gap. Unlike the mean effect, the results suggest that 1) tourism has the heterogeneous effect on poverty alleviation in terms of different poverty levels: in the case of very low quantiles of poverty, tourism does not seem to reduce poverty effectively; 2) compared with international tourism receipts, international tourism arrivals show a higher effect on poverty reduction; 3) tourism development contributes more than GDP growth on poverty alleviation; 4) higher tourism growth effects are found on headcount ratio rather than the poverty gap.